Model size effects on calculated electronic and bonding properties of adsorption sites in zeolites - Sánchez, Morella; Añez, Rafael; Sierraalta, Anibal; Rosa Brussin, Marcos; Soscum, Humberto; Ruette, Fernando (Ciencia)
A theoretical comparative study of NO adsorption on FeO-ZSM5 zeolite catalyst models was done using a quantum chemistry parametric method for catalysis (CATIVIC) with clusters of 19, 46, 123 and 327 atoms. Results show that the cluster model size is of fundamental importance for modeling NO catalytic adsorption. There is a notable strengthening of the Fe-N bond and a significant electronic transfer from adsorption site surroundings to the Fe atom, as the cluster model size increases. Theoretical methods, such as parametric ones, permit the utilization of large models that are relevant in modeling catalytic adsorption sites, because take into account geometrical and electronic long range effects.